(untitled) ("XXI ASRDA INNOVATSION TEXNOLOGIYALAR, FAN VA TAʼLIM TARAQQIYOTIDAGI DOLZARB MUAMMOLAR" nomli respublika ilmiy-amaliy konferensiyasi, 2024)
This article explores the importance of effective time management for educators in enhancing productivity and fostering progress in teaching. By examining strategies for prioritizing tasks, managing classroom time, and optimizing lesson planning, educators can create a conducive environment for student learning and professional growth.